Child care matters: what educated mothers need before entering the labor market / Suhaida Mohd Amin … [et al.] - Mohd Amin, Suhaida; Borhan, Halimahton; Ridzuan, Abd Rahim; Mat Saad, Rosfadzimi; Subramaniam, Geetha (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
Individuals who succeed in higher education are supposedly skillful with very high employability rates and predictable career outcomes. In parallel with that, recent statistics show increasing number of female graduates in higher institutions in Malaysia. However, comparing regional estimates of female participation rates in the labor market, Malaysian women have a relatively low participation in labor market for decades. Among the educated women surveyed in 2017, 42 percent were outside the labor force while the married ones said they did not work to look after their children. In this qualitative study, nine educated mothers and three experts in the field were interviewed to find the real problems related to child care. The three validated themes were child care costs, availability of child care centers and child care quality. A quality child care center is usually more expensive. Although many qualified centers have been established, not all meet the needs of discerning educated mothers who can choose not to enter or exit the labor market to look after their children.